Governing landscapes: An agenda for the assessment of grasslands and savannahs - Eufemia, Luca; Wawrzynowicz, Ingrid; Bonatti, Michelle; Partelow, Stefan; Fischer, Joern; Sieber, Stefan (Frontiers in Sustainable Resource Management, 2023)
In this article, we propose an agenda promoting the development of a new integrated assessment toolkit (theory-based toolkit) of environmental governance in overlooked ecosystems of grasslands and savannahs in the Global South. To explore the complexity of social-ecological and governance systems, a growing number of systems-thinking approaches provide academics/practitioners with numerous analytical frameworks, theories, and methodologies that are potentially useful for unveiling institutional aspects along with their causal variables for the access, use and management of natural resources. Yet, we argue that achieving a comprehensive understanding of environmental governance systems only by using one single framework or theory is limiting. Further, there is a growing need of more social science knowledge and grassland and savannah context-specific frameworks that are tailored and applicable to policy settings. Therefore, by building on the five approaches of the political ecological framework of community-based governance (CBG) relating to key environmental governance frameworks, such as the community-based natural resource management (CBNRM) and the institutional and development framework (IAD), we propose a theory-based toolkit that would review, synthesize, connect, relate and test multiple core principles in a way that more fully accounts for social-ecological interactions in focal ecosystems. We are convinced that future empirical analysis/research following our agenda and the toolkit approach can generate hypotheses that are testable in real-life contexts. To this end, we suggest guiding research questions, research methods, as well as comparable cases and their rationales.